Plasma parameters in pig with metal-hydride cathode under different ways of hydrogen supply - Sereda, I.N.; Tseluyko, A.F.; Ryabchikov, D.L.; Babenko, I.V.; Hrechko, Ya.O.; Hetman, V.A. (Вопросы атомной науки и техники, 2015)
In the paper plasma density dynamic on the axis of Penning discharge with metal-hydride cathode in axial electron flow emission regime have been experimentally investigated. The ion-stimulated desorption influence on emissive characteristics of the source were studied. Sufficient plasma density increasing up to n ≈ 10¹⁰ cm⁻³ was established on the discharge axis when metal-hydride cathode was used. Comparable analysis of the plasma density dynamic under different ways of hydrogen supply was carried out. Експериментально досліджена динаміка густини плазми на осі розряду Пеннінгa з металогідридним катодом у режимі емісії аксіального потоку електронів. Вивчено вплив іон-стимульованої десорбції водню на емісійні характеристики джерела. Встановлено значне збільшення щільності плазми n ≈ 10¹⁰ cm⁻³ на осі розряду з металогідридним катодом. Проведено порівняльний аналіз динаміки щільності плазми при різних способах напуску водню в розрядний проміжок. Экспериментально исследована динамика плотности плазмы на оси разряда Пеннинга с металлогидридным катодом в режиме эмиссии аксиального потока электронов. Изучено влияние ион-стимулированной десорбции водорода на эмиссионные характеристики источника. Установлено значительное увеличение плотности плазмы n ≈ 10¹⁰ cm⁻³ на оси разряда с металлогидридным катодом. Проведен сравнительный ана-лиз динамики плотности плазмы при различных способах напуска водорода в ячейку.